Drug of abuse talk and sharing session / Saliha Azlan - Azlan, Saliha (Faculty of Pharmacy, 2024)
The Drug of Abuse Talk and Sharing Session, organised collaboratively by students of the Drug of Abuse (PHC665) course and the Society of Pharmacy Students (SOPHYS) at Universiti Teknologi MARA, took place on 5th June 2024 at Dewan Kuliah 7, FF4, Faculty of Pharmacy, UiTM Puncak Alam Campus. This academic initiative was designed to provide participants, primarily students enrolled in PHC665 (Drug of Abuse), with an immersive exploration into the complexities of addiction, emphasizing both theoretical knowledge and practical insights into recovery methodologies.